Multi-Hop Retrieval Impact on Phi-3-Mini and Mistral-7B Accuracy in MuSiQue - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 4 peer-reviewed papers addressing the following research question: How does varying the number of retrieval hops affect the answer accuracy of Phi-3-mini compared to Mistral-7B on the MuSiQue dataset. 9 claims were extracted from source literature; 1 was independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 4.5/10. This report is a machine-generated literature synthesis and does not constitute
Machine-generated literature synthesis.